TINJAUAN ELIPSIS PADA KALIMAT KONDISIONAL BAHASA ARAB - Afnan Arummi (Arabic Literature Department, 2013)
One of the unique Arabic languages is an ellipsis system or one of the elementscontained in an utterance. Among the Arabic sentence systems getting ellipsis isconditional sentences (al-jumlah a‟sy-syarthiyyah). This article describes the study ofellipsis in Arabic conditional sentence reviewed from the linguistics perspective. Thediscussion in this study is focused on the theoretical concept of conditional sentences inArabic and the concept of ellipsis (hadzf) specifically. Syntactic approach is used in thisresearch to assess the grammatical structure as conditional markers, the relationshipbetween the clauses of conditional sentences, the relationship between conditionalsentences with other linguistic elements.